The impact of the mRNA COVID-19 vaccine on the Th-like cytokine profile in individuals with no history of COVID-19: insights into autoimmunity targeting heat shock proteins - Tukaj, Stefan; Sitna, Magdalena; Sitko, Krzysztof (Frontiers in Immunology, 2025)
Although some reports suggest that COVID-19 vaccination may exacerbate existing autoimmune diseases or trigger new-onset cases, a definitive causal relationship between the vaccines and these conditions has not been established. Several potential mechanisms have been proposed to explain this association, including: (i) molecular mimicry, which refers to a structural similarity between SARS-CoV-2 and human antigens; (ii) bystander activation, involving both B and T lymphocytes; and (iii) the effects of adjuvants. In this study, we investigated whether two doses of the mRNA COVID-19 vaccine influenced blood cytokine levels associated with major T helper cell populations, which are known to play a significant role in autoimmunity and revisited the role of the humoral autoimmune response directed against heat shock proteins (Hsps) in individuals with no history of COVID-19. While no significant differences were found in the levels of IFN-γ, IL-6, IL-22, IL-4, IL-8, IL-10, and IL-17A, between vaccinated and unvaccinated people, several positive correlations were observed between serum cytokine levels and circulating autoantibodies directed against self-Hsps exclusively in vaccinated individuals. These findings suggest that the mRNA COVID-19 vaccine does not impact cytokines involved in the pathogenesis of autoimmune diseases. Further research is required to evaluate the safety of COVID-19 vaccination in patients with autoimmune conditions, particularly those in whom anti-Hsps autoantibodies are suspected to contribute to disease development.